Sustenance of Entrepreneurship Culture: Requisite of Financial Literacy in Contemporary Nigerian Society - Martins Ojo Erinsakin (The Indonesian Institute of Science and Technology Research, 2026)
Business failure has been a national issue of growing concern in Nigeria, and the reasons are varied. A descriptive survey research design was used. The study population comprised entrepreneurship students in Nigeria. The sample size of the study was 1,080 respondents who were selected through a simple random sampling technique, using a set of structured questionnaires that were validated for the study. Data were generated through a self-structured questionnaire titled Questionnaire on Sustenance of Entrepreneurship Culture: Requisite of Financial Literacy in Contemporary Nigerian Society (SECFRLNS), fashioned on a four-point rating scale: Strongly Agree (SA), Agree (A), Disagree (D), and Strongly Disagree (SD), respectively, and 1 point, respectively. The research instruments were validated by experts in Measurement and Evaluation. Its reliability was determined through the test-retest method at two weeks interval. 0.70 coefficient reliability was established. A conclusion was made based on the results that financial literacy has no significant and positive influence on entrepreneurship culture in contemporary Nigerian society. Recommendations were made that the government should make the country secure for business activities. Besides, entrepreneurs should be assisted to source the initial capital from the conventional banking sector.